دور المحكمة الجنائية الدولية في النظر بجرائم تجنيد الأطفال - زودة, حلا; حماد, مسعود (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In this paper, we examine the crime of recruiting children, whether it is recruitment in international armed conflicts or non-international conflicts, as one of the war crimes stipulated by the Rome Statute of the International Criminal Court in Article 8, as stipulated in Article 488 bis of the Syrian Penal Code. By examining the substantive provisions that relate to that crime, which includes the nature of the crime and its elements, in addition to talking about the scope of the criminal responsibility and its scope and prohibitions and penalties for it and the legal status of the child recruits, and we will also discuss the procedural provisions through the identification of rules And we will talk about some practical examples of the crimes of recruitment of children in combat through the only case before the International Criminal Court on the crimes of child recruitment in the Democratic Republic of the Congo, and the current occurrence of armed groups in Syria To recruit children to participate in hostilities, and to indicate the position of the Syrian and international legislators. تتمحور دراستنا ضمن هذا البحث حول جريمة تجنيد الأطفال، سواء كان التجنيد في النزاعات المسلحة الدولية أو النزاعات غير الدولية، كإحدى جرائم الحرب التي نص عليها نظام روما للمحكمة الجنائية الدولية في المادة الثامنة منه، والمنصوص عليها في المادة 488 مكرر من قانون العقوبات السوري، وذلك من خلال البحث بالأحكام الموضوعية التي تخص تلك الجريمة التي تتضمن ماهية الجريمة وأركانها، بالإضافة إلى الحديث عن نطاق المسؤولية الجزائية ومداها وموانعها والعقوبات المقررة لها والمركز القانوني للطفل المجنّد، وسنبحث أيضاً في الأحكام الإجرائية من خلال تحديد القواعد الناظمة لتحريك اختصاص المحكمة، والجهات التي يحق لها ذلك، وسنقوم بالحديث عن بعض الأمثلة العملية لجرائم تجنيد الأطفال في القتال من خلال القضية الوحيدة التي نظرت أمام المحكمة الجنائية الدولية المتعلقة بجرائم تجنيد الأطفال في جمهورية الكونغو الديمقراطية، وما يحدث حالياً من قيام الجماعات المسلّحة في سوريا بتجنيد الأطفال لديهم للمشاركة بالأعمال القتالية، وبيان موقف المشرّع السوري والدولي من ذلك.